Industrial Economics : Economics Analysis and Public Policy - MARTIN, Stephen (Macmillan Publishing Company, 1994)
This industrial organization text develops analysis in a logical manner. Its central topic is the exercise of market power - the control of price and the exclusion of competitors. This edition contains detailed case studies and examples, including many international cases. Public policy is treated in parallel with corresponding theory and empirical evidence throughout.